Poltergeist - Hooper, Tobe (Turner Entertainment, 1997)
Fascinating frightening as suspenseful as they come, POLTERGEIST is high-voltage, jolt-a-minute filmmaking at its compelling best. Producer Steven Spielberg (E.T.Raiders Of the Lost Ark) here presents director Tobe Hooper 's extraordinary, ultra-fantastic excursion into the supernatural. Thanks to the wizardry of George Lucas' (Star Wars) Industrial Light and Magic, POLTERGEIST delivers a non-stop spectacle of visual effects you simply have to see to believe. Life is very pleasant for the the close-knit Freeling family until a host of other-worldly forces invades their peaceful suburban home. It starts with just an a odd occurrence or two, but soon their house is turned into a swirling supernatural sideshow. The forces at work are anything but friendly, and if the luckless Freelings don't clear out soon, they'll all be swept off into nightmarish chaos! Astounding, absorbing, yet laced with humor and warmth, POLTERGEIST is " a work of art... Full of spine-snapping chills!" (Time).